FAMILY SUPPORT IN THE FULFILLMENT OF NUTRITION OF FAMILY MEMBERS WITH HYPERTENSION - Desmon Wirawati (UNEJ e-Proceeding, 2017)
Background: Nutrition is one of the factor that influence the occurrence of hypertension and family as the main unit in health care family members with hypertension. The purpose of this research was to identify the correlation between family support and nutrition fulfillment of family members with hypertention of family support in fulfilling requirement of family member nutrition with hypertension. Methods: was quantitative descriptive correlation with cross sectional approach. The research instrument used was questionnaire with probability sampling technique in 71 respondents. Results: Found that 35.2% of families provided good support in meeting nutritional needs. The fulfillment of good nutrition requirement from family was 29,6%. p = 0.012 there is relationship between family support with family member nutrition fulfillment with hypertension. The implications of the research results are expected to develop a hypertension nutritionally conscious family-giving program with family involvement. Conclusions: The family is expected to provide support in fulfilling their need nutrsi family members by hypertension. Keywords: family support, hypertension, nutrition